Analysis on the large-scale development stage and analysis method of 5G industry applications - Shan LI; Jiawei LIU (Dianxin kexue)
In the two years since 5G was officially put into commercial use in China, the Central Government had made frequent statements and attached great importance to the development and application of 5G.All parties in the industry had made positive progress technical standards, network construction and industrial development, laying a solid foundation for the development of 5G industry applications.The development status and challenges of 5G industry applications were comprehensively analyzed, the pattern of 5G standard and technological innovation transformation was studied, the application development stage and future development path of the 5G industry based on the development rule of each industry sector was analyzed, and the large-scale development of the 5G industry applications was prospected.